2011
DOI: 10.1093/cid/cir375
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Nonclinical Health Care Workers Faced a Similar Risk of Acquiring 2009 Pandemic H1N1 Infection

Abstract: Reporting of confirmed pandemic influenza A virus (pH1N1) 2009 infection was mandatory among health care workers in Hong Kong. Among 1158 confirmed infections, there was no significant difference in incidence among clinical versus nonclinical staff (relative risk, 0.98; 95% confidence interval, 0.78-1.20). Reported community exposure to pH1N1 was common and was similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…In contrast to a finding by Kawana et al ( 16 ), neither our study nor those of Marshall et al and Seto et al detected an increased risk for influenza among workers who had direct patient care responsibilities ( 17 ). However, Marshall et al indicated that working in an intensive care unit of a hospital was a risk factor for influenza, and wearing gloves while caring for patients who were on droplet precaution was protective.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to a finding by Kawana et al ( 16 ), neither our study nor those of Marshall et al and Seto et al detected an increased risk for influenza among workers who had direct patient care responsibilities ( 17 ). However, Marshall et al indicated that working in an intensive care unit of a hospital was a risk factor for influenza, and wearing gloves while caring for patients who were on droplet precaution was protective.…”
Section: Discussioncontrasting
confidence: 99%
“…We previously estimated that around 10%–15% of HCWs were infected through the first wave and cumulative incidence of infection was higher in younger HCWs [4] although the majority of infections were not confirmed by laboratory testing [3]. Higher pH1N1 antibody seroprevalence in younger HCWs who reported receipt of pH1N1 vaccine (Table 1) could be associated with a greater risk of infection rather than better immunogenicity [4], [12].…”
Section: Discussionmentioning
confidence: 98%
“…We observed no documented nosocomial transmission during the study period. Although influenza A (H1N1) viruses that carry the H275Y mutation have been shown to demonstrate reduced transmissibility in animal model [10], it remains unclear whether this also occurs in humans infected with A(H1N1)pdm09 [11,12].…”
Section: Discussionmentioning
confidence: 99%